Lithuania : Investment Climate Assessment - World Bank (Washington, DC, 2012)
The World Bank undertook an investment climate assessment in Lithuania in 2004 as part of its efforts to support member countries through in-depth analysis of major microeconomic constraints in their business environments. Lithuania has made serious efforts in recent years to improve its investment climate. This report has attempted to capture as much as possible the achievements of those efforts as well as the shortcomings that remain. The general picture in 2004 was of impressively rapid progress in the previous two to three years. Yet Lithuania remains unable to attract significant amounts of foreign direct investment. Its small market with limited purchasing power, and its record as a slow reformer in the 1990s compared with peer countries, may be objective constraints. The report findings highlight impressive improvements in Lithuania's investment climate in the past few years, and conclude with a list of recommended actions for improving Lithuania's investment climate.